2003
DOI: 10.1002/app.12672
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new polymeric hindered amine light stabilizers: Performance evaluation in styrenic polymers

Abstract: Polymeric hindered amine light stabilizers (HALSs), in which the HALS functionality was attached to the terminal isocyanate chain end of poly(styryl-co-styryl isocyanate), were synthesized by a two-step process. First, cinnamoyl azide was prepared and copolymerized with styrene by a free-radical copolymerization method. Polymeric low-molecular-weight and high-molecular-weight 2,2,6,6-tetramethyl-4-pipridinol-graft-poly(styryl-co-styryl isocyanate) and 4-amino-2,2,6,6-tetramethyl piperidine-graft-poly-(styryl-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…63 In specialized applications where brightening is important, as in textile or paper substrates, the additive may have considerable advantages over conventional technology. Singh et al 64 reported the synthesis of a novel HALS-type polymeric stabilizer and demonstrated its effectiveness on high-impact polystyrene to be superior to that of conventional light stabilizers. This improvement is likely a result of reduced leaching of stabilizer from the matrix.…”
Section: Recent Developments In Halsmentioning
confidence: 99%
“…63 In specialized applications where brightening is important, as in textile or paper substrates, the additive may have considerable advantages over conventional technology. Singh et al 64 reported the synthesis of a novel HALS-type polymeric stabilizer and demonstrated its effectiveness on high-impact polystyrene to be superior to that of conventional light stabilizers. This improvement is likely a result of reduced leaching of stabilizer from the matrix.…”
Section: Recent Developments In Halsmentioning
confidence: 99%
“…The synthesis of HALS of higher molecular weight by addition or condensation copolymerizations [9][10][11] or the grafting of photostabilizers onto the preformed polymer [12][13][14][15][16] are usual strategies described by the literature to eliminate or minimize such undesirable effects. The preparation of polymeric HALS by the copolymerization of hindered amines with ethylene or propylene is also an alternative route to reduce their physical loss [17,18] .…”
Section: Introductionmentioning
confidence: 99%
“…Besides substantially reducing the HALS efficiency and therefore the product's lifespan, physical loss can cause serious toxicity problems. The synthesis of polymeric HALS, with optimal molecular weight and molecular architecture more compatible with different polymeric matrix has been an important alternative to achieve a long-term stabilizing effect and minimize the physical loss of HALS [18][19][20] . Polymeric HALS can be prepared by the copolymerization of vinyl monomers containing HALS group or macromolecular functional reaction [21,22] .…”
Section: Introductionmentioning
confidence: 99%